(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Kaseesa is classified under two groups - Uparasa and Upadhatu. It is a mineral drug used in therapeutics. Hence Shodhana should be done before further use in as therapeutics or for preparation of Bhasama. The objective of this article is to compare pharmaceutical and Analytical aspects of Ashuddha Kaseesa and Shuddha Kaseesa (Sodhana with different methods). Material and Methods: Present study aimed to compare different Shodhana methods of Kaseesa which is by Bhavana in Bhringaraja Swarasa, Swedana in Bhringaraja Swarasa, Bhavana in Nimbu Swarasa and Bhavana in Citric acid solution rather than Nimbu Swarasa. The preliminary physico-chemical analysis was performed simultaneously for the Ashuddha and different samples of Shuddha Kaseesa (Shodhana by different methods). The total Iron contain and total inorganic contain were carried out by EW-XRF Spectroscopy technique. Results: After Shodhana with different methods average yield of Shuddha Kaseesa was 99.72%, 108.33%, 96% and 84% method A, B, C and D simultaneously. Total iron concentration of AK was 26.28. Significant physical changes have been observed after Shodhana. Which reflects in BBK, SBK, MNK and MCK has 23.52, 21.96, 26.6 and 41.46 percentage of total iron contain. Conclusion: Pharmceutico-analytical study revealed that there were major physical and chemical changes occurs after Shodhana in Kaseesa. Each method and liquid media led to major physical and chemical changes in Kaseesa. Which also reflects in total iron contain of Shuddha Kaseesa as compare to Ashuddha.